1992
DOI: 10.1002/mrm.1910270105
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear magnetic resonance investigation of the upper airways in ferrets. ii. contrast‐enhanced imaging to distinguish vascular from other nasal fluids

Abstract: Proton magnetic resonance imaging (MRI), used in conjunction with the intravascular contrast agent albumin-(Gd-DTPA), provides a means to distinguish vascular fluids from other nasal fluids in the upper airways. Ferrets were given an intravenous dose of albumin-(Gd-DTPA) followed by an intranasal challenge with either histamine (HS) or methacholine (MC). An observed increase in image intensity indicates that HS and MC both cause an accumulation of fluids in the nasal turbinate region. The MRI data are also inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is the first study in man to evaluate nasal allergen responses using MRI imaging before and after nasal allergen challenge. Animal studies have reported the effect of nasal challenge in response to histamine and methacholine on MRI images using gadolinium enhancement to localize edema formation . Clinically, MRI has mainly been used for the evaluation of the para‐nasal sinuses and may replace CT for the evaluation of pathological mucosal abnormalities .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study in man to evaluate nasal allergen responses using MRI imaging before and after nasal allergen challenge. Animal studies have reported the effect of nasal challenge in response to histamine and methacholine on MRI images using gadolinium enhancement to localize edema formation . Clinically, MRI has mainly been used for the evaluation of the para‐nasal sinuses and may replace CT for the evaluation of pathological mucosal abnormalities .…”
Section: Discussionmentioning
confidence: 99%